Kesadaran Palsu di Balik Interaksi Pelanggan Coffee Shop dengan Barista - Dinar, Yuceu Aprilya Prastica (Prodi Sosiologi FISIP ULM, 2025)
A barista is one of the coffee shop workers who frequently interacts with customers, making them an essential aspect that attracts customers to visit a coffee shop. This study aims to explore in greater depth the relationships that emerge from the interactions between baristas and coffee shop consumers. The research employs a qualitative approach to help the researcher uncover systematic findings and provide in-depth explanations. Through observation and in-depth interviews, the study illustrates how Tengah Hari Coffee develops strategies to attract customers. The findings reveal that the role of a barista in the growth of a coffee shop is highly dominant. Baristas serve as the first point of contact and often become the central element of the customer experience. Their role extends beyond merely preparing coffee; they also significantly influence the overall customer experience and play a crucial part in the success of a coffee shop. Baristas additionally employ strategies to increase sales, such as offering a complimentary cup of latte art to loyal customers. This practice, as seen at Tengah Hari Coffee, is sometimes misinterpreted by certain customers, leading to the emergence of false consciousness within the customer-barista interaction. This study contributes to a better understanding of the reciprocal relationship between baristas and consumers by offering a new perspective. To further develop this research, future scholars could analyze the phenomenon using different theoretical frameworks, allowing it to be examined from multiple perspectives